2020
DOI: 10.1016/j.neuropharm.2019.107930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-dose antipurinergic therapy on behavioral and molecular alterations in the valproic acid-induced animal model of autism

Abstract: Autism spectrum disorder (ASD) is characterized by deficits in communication and social interaction, restricted interests, and stereotyped behavior. Environmental factors, such as prenatal exposure to valproic acid (VPA), may contribute to the increased risk of ASD. Since disturbed functioning of the purinergic system has been associated with the onset of ASD and used as a potential therapeutic target for ASD in both clinical and preclinical studies, we analyzed the effects of suramin, a nonselective purinergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…Β-3-tubulin was used as a normalizer for this experiment (Forward: AGACC-TACTGCATCGACAATGAAG Reverse: GCTCATGG-TAGCAGACACAAGG). Beta-3-tubulin was chosen as a housekeeping gene based on a previous report (Hirsch et al, 2019) and on the analysis performed by the BestKeeper calculation, an excel-based tool using pairwise correlations (Pfaffl et al, 2004), which shows that it is the most stable housekeeping gene in cortical samples from VPA animals (Figure S1). This analysis considered the standard deviations included in Table S1.…”
Section: Tissue Samples and Rt-qpcr Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Β-3-tubulin was used as a normalizer for this experiment (Forward: AGACC-TACTGCATCGACAATGAAG Reverse: GCTCATGG-TAGCAGACACAAGG). Beta-3-tubulin was chosen as a housekeeping gene based on a previous report (Hirsch et al, 2019) and on the analysis performed by the BestKeeper calculation, an excel-based tool using pairwise correlations (Pfaffl et al, 2004), which shows that it is the most stable housekeeping gene in cortical samples from VPA animals (Figure S1). This analysis considered the standard deviations included in Table S1.…”
Section: Tissue Samples and Rt-qpcr Proceduresmentioning
confidence: 99%
“…The tissues were then homogenized in TRIzol ® reagent (Invitrogen ® , USA) in a proportion of 10 μl of TRIzol ® per milligram of tissue and preserved at ultrafreezer (À80 C) until further molecular analysis. After homogenization of tissue samples, RNA extraction and RT-qPCR analysis for LHX6 gene expression were performed as previously described (Hirsch et al, 2019). The PCR mix contained 12 μl of cDNA (1:33), 1.0 μl of specific miRNA forward and universal reverse (10 μM) primers, 0.5 μl of 10-μM dNTP mix, 2.4 μl of 10Â PCR buffer (Invitrogen, USA), 0.8 μl of 50-mM MgCl2 (Invitrogen, USA), 2.4 μl of 1Â SYBR™ Green (Molecular Probes, USA), 0.1 μl of Platinum Taq DNA Polymerase (Invitrogen, USA) and sterile distilled water totaling a final volume of 24 μl.…”
Section: Tissue Samples and Rt-qpcr Proceduresmentioning
confidence: 99%
“…However, the specific genetic differences between mouse strains, and even specific mutations leading to ASD, appear not to have a significant effect on purinergic signaling associated with ASD-like behaviors. Several groups have now shown that treatment with the antipurinergic drug suramin was able to correct all the behavioral abnormalities, and most of the metabolic abnormalities, in the MIA model in C57Bl/6J mice, the Fragile X model in FVB mice [1][2][3], a rat model of ASD caused by prenatal exposure to valproic acid [149], and in a small clinical trial in children with ASD [4]. Metabolomic analysis after correction of the ASD-associated behaviors showed that the top metabolic pathway changed by treatment in all of these studies was purines [1,2,4].…”
Section: Limitationsmentioning
confidence: 99%
“…However, the speci c genetic differences between mouse strains, and even speci c mutations leading to ASD, appear not to have a signi cant effect on purinergic signaling associated with ASD-like behaviors. Several groups have now shown that treatment with the antipurinergic drug suramin was able to correct all the behavioral abnormalities, and most of the metabolic abnormalities, in the MIA model in C57Bl/6J mice, the Fragile X model in FVB mice [1][2][3], a rat model of ASD caused by prenatal exposure to valproic acid [111], and in a small clinical trial in children with ASD [4]. Metabolomic analysis after correction of the ASD-associated behaviors showed that the top metabolic pathway changed by treatment in all of these studies was purines [1,2,4].…”
Section: Limitationsmentioning
confidence: 99%